Struktura prywatnych wydatków na zdrowie na osobę w krajach UE w latach 2008–2018 - Banaszczak-Soroka, Urszula (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
Classification of Individual Consumption by Purpose (COICOP). Make health expenditure accepted in European Union statistics into three main categories: medical and pharmaceutical products, medical devices and equipment; outpatient and alternative medicine services, hospital and sanatorium services. This classification also applies to private households on health as part of consumption. The aim is to investigate the structure of health expenditure per capita in the EU-27 in the years 2008–2018.
Keywords: consumption; health expenditure; classification of individual consumption by purpose